2021
DOI: 10.1096/fj.202002159r
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptors can control the Hippo/YAP pathway through Gq signaling

Abstract: The Hippo pathway is an evolutionarily conserved kinase cascade involved in the control of tissue homeostasis, cellular differentiation, proliferation, and organ size, and is regulated by cell‐cell contact, apical cell polarity, and mechanical signals. Miss‐regulation of this pathway can lead to cancer. The Hippo pathway acts through the inhibition of the transcriptional coactivators YAP and TAZ through phosphorylation. Among the various signaling mechanisms controlling the hippo pathway, activation of G12/13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…115 The Hippo pathway has been shown to be regulated by GPCR signalling. [116][117][118][119] For example, it was shown that GPCR ligands such as thrombin or lysophosphatidic acid (LPA) could activate YAP in fibroblasts and sensitize them to TGF-β1. 120 Additionally, sphingosine-1-phosphate (SIP) is a ligand of GPCR.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…115 The Hippo pathway has been shown to be regulated by GPCR signalling. [116][117][118][119] For example, it was shown that GPCR ligands such as thrombin or lysophosphatidic acid (LPA) could activate YAP in fibroblasts and sensitize them to TGF-β1. 120 Additionally, sphingosine-1-phosphate (SIP) is a ligand of GPCR.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…GPCR inhibitors have also been describe to inhibit YAP/TAZ-TEAD indirectly ( Cunningham and Hansen, 2022 ). For instance, YM-254890, a specific G(α)q/11 inhibitor that indirectly inhibits YAP/TAZ ( Zindel et al, 2021 ), inhibited IH in a mouse model of vascular injury ( Kawasaki et al, 2005 ). However, YM-254890 also reduced systemic blood pressure and no further investigations were made in the context of IH ( Kawasaki et al, 2005 ).…”
Section: Treatment Of Intimal Hyperplasiamentioning
confidence: 99%
“…It is well established that Hippo-YAP pathway is emerging as important player in various types of cancers [27]. For example, in prostate cancer, inhibition of the Hippo-YAP pathway is su cient to activate apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%